Two‐point boundary value problems at resonance - Yermachenko, Inara (Mathematical Modelling and Analysis, 2009)
Consider two‐point boundary value problems of resonance type x″ +x = f(t, x, x′), x(0) = x(π) = 0. We investigate existence and multiplicity of solutions to such problems by using the quasilinearization process.First published online: 14 Oct 2010